Middle Jurassic Ammonites from The Cendrawasih Bay Coast and North Lengguru Fold-Belt, West PApua: Implications of a ‘Forgotten’ 1913 Paper - van Gorsel, J.T. (Han) (Ikatan Ahli Geologi Indonesia, 2012)
Occurrences of Middle Jurassic bathyal shales with typical ammonite faunas were reported from the 'Birds Neck', West Papua, in 1913 and 1927 publications but these appear to be largely forgotten. They signify an eastern limit for the gas-productive Middle Jurassic sands of Bintuni Bay and thus have significant negative implications for the potential of Mesozoic hydrocarbon plays in Cenderawasih Bay.